Emotional-based pedagogy and facilitating EFL learners' perceived flow in online education - Abdolrezapour, Parisa; Ghanbari, Nasim (Frontiers in Psychology, 2022)
Given the fundamental role of emotional intelligence (EI) in learning, especially in virtual learning contexts where individuals experience more stress and anxiety, the need to understand and recognize one’s own feelings and the mutual feelings of peers has gained more importance. Flow as the ultimate state in harnessing emotions in the service of performance and learning has been introduced as the main reason for one’s willingness to perform activities which are connected to no external motivation. In this regard, the present study was conducted to first introduce a new educational program to enhance the EI level in the English as a foreign language (EFL) online education environment and next to investigate the possibility of raising EFL learners’ perceived flow. To achieve these goals, the study recruited a sample of 67 EFL learners who were next divided into experimental (n = 32) and control (n = 35) groups. The experimental group received the EI intervention over ten weeks and the control group received the ordinary online EFL instruction. Data were collected through EI and flow questionnaires and semi-structured interviews which focused on learners’ perception of the EI intervention and signs of enhanced flow. Statistical analysis of the data showed a positive effect of the program on the learners’ EI and their perceived flow. The study emphasizes the role of applying positive emotions in making language learners more engaged in online classroom tasks.